REINTERPRETATION OF SEXUAL ETHICS IN THE HADITH THROUGH MUHAMMAD SHAHRUR'S THEORY OF LIMITS - Ridwan; Hendri Sayuti; Bambang Hermanto (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
The discourse on sexuality in classical Islamic law often places women in a passive position, prioritizing the husband's sexual rights over the wife's satisfaction. This article aims to explore Muhammad Shahrur's thoughts on sexual ethics within marriage, specifically regarding the prophetic tradition (hadith) that prohibits stopping sexual intercourse before the wife achieves climax. Utilizing a qualitative methodology with a library research approach, this study analyzes the text of the hadith through the framework of Shahrur’s Limit Theory (Nazariyyah al-Hudud). The results indicate that from Shahrur's perspective, a wife’s sexual satisfaction is not merely a moral recommendation (sunnah), but rather serves as al-hadd al-adna (the lower limit or minimum threshold) that must legally be fulfilled to maintain justice within the marital relationship. This reinterpretation shifts the traditional, patriarchal understanding of Islamic jurisprudence toward a framework rooted in human rights, medical science, and gender equality. Consequently, this study provides a theoretical foundation for reforming Islamic family law regarding reproductive rights and preventing marital sexual deprivation.